Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Google-Books-ID: qJwRvgAACAAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé